Long-term follow-up of combination therapy with pembrolizumab and anlotinib in thoracic SMARCA4-deficient undifferentiated tumor: a case report and molecular features - Duan, Ting; Xu, Mingxin; Zhang, Haibo; Wu, Shengchang; Wang, Haochu; Guo, Zhenying (Frontiers in Oncology, 2024)
Thoracic SMARCA4-deficient undifferentiated tumors (SMARCA4-UTs), recently recognized as a rare malignancy described in the 5th edition of the World Health Organization Classification of Tumors, are characterized by an inactivating mutation in SMARCA4, most commonly found in the mediastinum of male smokers. Despite the aggressive nature and poor prognosis associated with these tumors, which have a median survival time of approximately 4-7 months, no standardized treatment guidelines are currently established. There are currently no reported cases of extended progression-free survival (PFS) in SMARCA4-UT patients treated with surgery and immunotherapy. Here, we report the clinical features and genomic information of a SMARCA4-UT case in which the patient responded significantly to a combination therapy involving surgery, immunotherapy, and amlotinib. A 56-year-old male non-smoker presented with a mass in the superior lobe of left lung and left hilar adenopathy. A left upper lobectomy and lymphadenectomy were performed, and postoperative pathology confirmed that the tumor was Thoracic SMARCA4-UT. The patient subsequently received chemotherapy with pemetrexed and carboplatin. Five months post-operation, the disease progressed with left adrenal metastasis and mediastinal adenopathy. An adrenalectomy was performed, followed by whole exon sequencing (WES). SMARCA4, SMARCA2 and SMARCA1 gene mutations were detected in this case. Given a tumor proportion score (TPS) of 60% for programmed death-ligand 1(22C3)immunoexpression and high TMB(361.32 muts/Mb), a combination of Pembrolizumab plus anlotinib was initiated as a second-line approach. After 46 cycles, the patient demonstrated no disease progression with a PR lasting 31 months and long progression-free survival(PFS) of 43 months. The lung tumor was initially detected in September 2020, and the patient remained alive at the latest follow-up in November 2024. This case offers a long-term follow-up of the effectiveness and safety of combining pembrolizumab and anlotinib in advanced SMARCA4-UT, and substantiates the role of long-term immunotherapy in preventing radiographic/clinical recurrence following surgery. This case illustrates new potential efficacy of immunotherapy in combination with surgery as a treatment approach of SMARCA4-UT.